Preconception Care Uptake and Immediate Outcomes among Discordant Couples Accessing Routine HIV Care in Kenya - Nyawira Gitahi; Sheila Juliet Eshiwani; Kenneth Mutai; Jared Ongechi Mecha; James Njogu Kiarie (Hindawi Limited, 2020)
Introduction. A large proportion of new HIV infections occur within discordant partnerships making discordance a significant contributor to new HIV infections in Africa. Despite the role of preconception care for HIV discordant couples, there is little data on fertility desire and preconception care uptake. This study aimed at documenting fertility desire (desire to conceive), determining the uptake of preconception care, identifying HIV prevention strategies used during preconception care, and determining immediate conception outcomes among HIV discordant couples in Kenya. Methods. We retrospectively extracted electronic medical record data on discordant couples at an HIV care discordant couples' clinic. We included data on couples who expressed a desire to conceive and were offered preconception care and followed up for 29 months. We collected data on sociodemographic characteristics, preconception prevention methods, and associated outcomes. Results. Among couples, with male HIV-positive partners, there was a twofold likelihood of accepting preconception services (OR = 2.3, CI 95% (1, 1, 5.0)). A shorter discordant union was independently associated with the uptake of preconception services (OR = 0.92, CI 95% (0.86, 0.98)). The most used prevention intervention (38.5%) among discordant couples was a combination of pre-exposure prophylaxis (PrEP) by the uninfected partner, alongside HAART by the partner living with HIV. Pregnancy rates did not significantly (p = 0.06) differ among those who took up preconception care versus those who did not. HIV-negative partners of couples who declined preconception care had a significantly (p = 0.04) higher attrition from clinic follow-up. One confirmed seroconversion occurred; an HIV incidence rate of 0.19 per 100 person-years.Conclusion. The study demonstrates the feasibility of implementing safe and effective preconception servicesas part of routine HIV care for discordant couples living in low resource settings. The provision and the utilisation of safer conception services may be hindered by the poor retention to follow-up and care of HIV-negative partners. This challenge may impede the expected benefits of preconception care as an HIV prevention intervention.